SODIUM HYALURONATE EYE DROPS IN THE TREATMENT OF DRY EYE DISEASE: AN OPEN LABEL, UNCONTROLLED, MULTI-CENTRE TRIAL - Cheema, Alyscia; Aziz, Tariq; Mirza, Sajid Ali; Siddiqi, Ahson; Maheshwary, Neeta; Khan, Muhammad Athar (Journal of Ayub Medical College Abbottabad, 2012)
Background: Dry eye disease (DED) is one of the most frequently encountered ocular morbidities. The objective of this study was to assess the performance of sodium hyaluronate eye drop for eight weeks in patients with DED. Patients and Methods: This was a multi-centre, open-label, uncontrolled clinical trial carried out at different centres of Pakistan, from August 2009 to November 2010. A total of 250 diagnosed patients of Dry Eye who met the inclusion criteria were included in the study. After informed written consent, all patients having at least 2 of the Dry Eye symptoms, and at least 1 of the tests (Tear Film Break-up time (TBUT) ‰¤10 second, Schirmer’s test ‰¤6 mm/5 min, and positive corneal staining) were enrolled. Tolerability/safety assessments consisted of monitoring and recording of adverse events and physical examinations at baseline, 4th week and 8th week. Results: Out of 250 allocated patients 13 dropped out. The mean age of the patients was 47.6±13.8 year and out of 237 patients 86 (36.3%) were men and 151 (63.7%) were women. At the initial visit the foreign body sensation was 80%, itching 68%, burning 58%, watering 38%, photophobia 38%, and feeling of dryness was 16%. At the 3rd visit the foreign body sensation decreased to 32%, itching to 32%, burning to 20%, watering to 12%, photophobia to 18%, and feeling of dryness to 14%. Conclusion: Sodium hyaluronate has a beneficial effect on the conjunctival epithelium in a well-defined and homogeneous population of patients with dry eye and can be considered useful for the treatment of dry eye. Keywords: Fluoresce in eye stain, Tear Break up Time, Schirmer’s test, Dry Eye Disease